2021
DOI: 10.1002/aelm.202100810
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of Polarization in Ferroelectric Ionic Conductors

Abstract: Ferroelectrics that are also ionic conductors offer possibilities for novel applications with high tunability, especially if the same atomic species causes both phenomena. In particular, at temperatures just below the Curie temperature, polarized states may be sustainable as the mobile species is driven in a controlled way over the energy barrier that governs ionic conduction, resulting in unique control of the polarization. This possibility is recently demonstrated in CuInP2S6, a layered ferroelectric ionic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…DFT molecular dynamics simulations have indeed confirmed that Cu atoms transfer from the – LP to the + LP sites independently (asynchronously, not synchronously as sheets) . Calculations of the gradual evolution of the polarization based on asynchronous Cu migration have been reported . Along the same lines, we calculated the diagonal elements of the CIPS dielectric tensor using standard perturbation theory for the LP-polarized state, two near-paraelectric states with different Cu arrangements in the ± LP states (see Figure S5), and a paraelectric ± LP state.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…DFT molecular dynamics simulations have indeed confirmed that Cu atoms transfer from the – LP to the + LP sites independently (asynchronously, not synchronously as sheets) . Calculations of the gradual evolution of the polarization based on asynchronous Cu migration have been reported . Along the same lines, we calculated the diagonal elements of the CIPS dielectric tensor using standard perturbation theory for the LP-polarized state, two near-paraelectric states with different Cu arrangements in the ± LP states (see Figure S5), and a paraelectric ± LP state.…”
Section: Resultsmentioning
confidence: 69%
“…12 Calculations of the gradual evolution of the polarization based on asynchronous Cu migration have been reported. 51 Along the same lines, we calculated the diagonal elements of the CIPS dielectric tensor using standard perturbation theory for the LPpolarized state, two near-paraelectric states with different Cu arrangements in the ± LP states (see Figure S5), and a paraelectric ± LP state. We found that ϵ ij remains roughly constant, with ϵ xx = ϵ yy ≈ 9 and ϵ zz ≈ 6.7, in good agreement with the average dielectric constant measured below the Curie temperature (Figure 3l).…”
Section: Resultsmentioning
confidence: 99%
“…However, because the vacancies may not be evenly distributed to each channel, it may be challenging to experimentally detect the exact change in quantum polarization in a single crystal. Additionally, the induced polarization can be greatly diminished in some systems, and a case in point is layered CuInP 2 S 6 , with the ion-conducting channels crossing the layers perpendicularly. Herein, Cu ions migrate across the van der Waals gaps, and the weak interlayer charge transfer makes InP 2 S 6 layers after the deintercalation of Cu ions at one side still almost neutral.…”
mentioning
confidence: 99%
“…, where four O-ions move for 1/2 lattice and leaves the unchanged. Alternatively, to describe the observations in piezoelectric microscopy experiments, a multireference scheme (MR) can be pragmatic 7,14 (dashed lines of Fig. 1b), owning to the phase-independent nature of proper piezoelectric response 18 .…”
Section: Full Textmentioning
confidence: 99%
“…Despite implied by O'Hara et al 14 , it is necessary to carefully revisit the rigorous application of modern theory of polarization (MTP) 15 in type-II FE ionic conductors. As a bulk property, the de nition of electric polarization P in MTP is based on Berry phase or equivalently on Wannier centers, both built from Bloch wavefunctions.…”
Section: Full Textmentioning
confidence: 99%